2006
DOI: 10.1093/toxsci/kfj205
|View full text |Cite
|
Sign up to set email alerts
|

Thimerosal Induces Apoptosis in a Neuroblastoma Model via the cJun N-Terminal Kinase Pathway

Abstract: The cJun N-terminal kinase (JNK)-signaling pathway is activated in response to a variety of stimuli, including environmental insults, and has been implicated in neuronal apoptosis. In this study, we investigated the role that the JNK pathway plays in neurotoxicity caused by thimerosal, an ethylmercury-containing preservative. SK-N-SH cells treated with thimerosal (0-10 microM) showed an increase in the phosphorylated (active) form of JNK and cJun with 5 and 10 microM thimerosal treatment at 2 and 4 h. To exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Previous studies have demonstrated that ROS mediates MAPK and c-Jun activation in various cellular stress conditions and cell types (4,26,28). To investigate the molecular mechanism underlying MAPK and c-Jun activation, cells were pretreated with an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ROS mediates MAPK and c-Jun activation in various cellular stress conditions and cell types (4,26,28). To investigate the molecular mechanism underlying MAPK and c-Jun activation, cells were pretreated with an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous injection of sufficient high quantities of thimerosal may cause inflammatory responses (Uchida et al, 1994). In recent years, there were several studies showing that thimerosal could induce apoptosis in a neuroblastoma model via the cJun N-terminal kinase pathway (Herdman et al, 2006). In T cells and neuronal cells, thimerosal causes apoptosis through mitochondrial pathways (Makani et al, 2002;Yel et al, 2005), and in human leukemia cells it also induced G2/M phase arrest (Woo et al, 2006).…”
Section: Thimerosalmentioning
confidence: 99%
“…Thimerosal alters the activity of sodium channels (Evans & Bielefeldt, 2000) and Ca 2+ -activated K + channels (Lang et al, 2000). It was reported that thimerosal induced DNA and membrane damage, caspase-3-dependent apoptosis (Baskin et al, 2003), activation of caspase-9 and caspase-3 (Makani et al, 2002), and activation of the cJun N-terminal kinase pathway (Herdman et al, 2006). Data showed that thimerosal and not thiosalicylic acid induced apoptosis in T cells (Makani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%